Effects of two wood-based biochars on the fate of added fertilizer nitrogen—a 15N tracing study - Kalu, Subin; Oyekoya, Gboyega Nathaniel; Ambus, Per; Tammeorg, Priit; Simojoki, Asko; Pihlatie, Mari; Karhu, Kristiina (Biology and fertility of soils, 2021)
A 15 N tracing pot experiment was conducted using two types of wood-based biochars: a regular biochar and a Kon-Tiki-produced nutrient-enriched biochar, at two application rates (1% and 5% (w/w)), in addition to a fertilizer only and a control treatment. Ryegrass was sown in pots, all of which except controls received 15 N-labelled fertilizer as either 15 NH 4 NO 3 or NH 4 15 NO 3 . We quantified the effect of biochar application on soil N 2 O emissions, as well as the fate of fertilizer-derived ammonium (NH 4 + ) and nitrate (NO 3 − ) in terms of their leaching from the soil, uptake into plant biomass, and recovery in the soil. We found that application of biochars reduced soil mineral N leaching and N 2 O emissions. Similarly, the higher biochar application rate of 5% significantly increased aboveground ryegrass biomass yield. However, no differences in N 2 O emissions and ryegrass biomass yields were observed between regular and nutrient-enriched biochar treatments, although mineral N leaching tended to be lower in the nutrient-enriched biochar treatment than in the regular biochar treatment. The 15 N analysis revealed that biochar application increased the plant uptake of added nitrate, but reduced the plant uptake of added ammonium compared to the fertilizer only treatment. Thus, the uptake of total N derived from added NH 4 NO 3 fertilizer was not affected by the biochar addition, and cannot explain the increase in plant biomass in biochar treatments. Instead, the increased plant biomass at the higher biochar application rate was attributed to the enhanced uptake of N derived from soil. This suggests that the interactions between biochar and native soil organic N may be important determinants of the availability of soil N to plant growth.